Evaluation value and mechanism of ADRB2 and FCER1B gene polymorphisms in preterm infants with congenital respiratory diseases: ADRB2, FCER1B polymorphisms and congenital respiratory - Liu, Jiangyue; Zhu, Qingwen; Jiang, Hongru; Zhang, Lingli; Cao, Xian (Cellular and Molecular Biology, 2023)
In this study, we observed the value of ADRB2 and FCER1B gene polymorphisms in evaluating congenital respiratory diseases in preterm infants (PTIs), analyzed their effects on airway smooth muscle cells (ASMCs), and preliminarily discussed the underlying mechanism. First, we placed 64 healthy PTIs (control group) and 45 PTIs with congenital respiratory diseases (research group) born at our hospital from April 2021 to June 2023 were selected as the research subjects. Through testing, we found that the carriers of AA genotype of the polymorphic marker rs1042713 of the ADRB2 gene and that of the rs569108 locus of the FCER1B gene were less in the research group compared with the control group (P<0.05). Preterm infants carrying the GG genotype had a 2.887-fold (P<0.05) increased risk of developing congenital respiratory disease under the recessive model at the rs1042713 locus of the ADRB2 gene. Under the dominant model, preterm infants who did not carry the AA genotype had a 3.070-fold (P<0.05) increased risk of developing congenital respiratory disease. Subsequently, the constructed abnormal expression vectors of ADRB2 and FCER1B were transfected into ASMCs to examine changes in cell activity and pyroptosis. We found that up-regulating ADRB2 and FCERIB expression promoted ASMC proliferation and inflammatory reactions, inhibited apoptosis, and accelerated pyroptosis (P<0.05); silencing their expression, however, led to the opposite effect. In conclusion, the ADRB2 and FCERIB gene polymorphisms are strongly correlated with congenital respiratory diseases, which can provide a reference for clinical evaluation of congenital respiratory diseases in PTIs.